Hierarchical CoO microflower film with excellent electrochemical lithium/sodium storage performance. Issue 39 (27th September 2017) - Chang, Ling; Wang, Kai; Huang, Liang-ai; He, Zhishun; Zhu, Shasha; Chen, Miaomiao; Shao, Haibo; Wang, Jianming
Abstract : The hierarchical CoO microflower film prepared by a low-temperature solvothermal method shows excellent electrochemical lithium/sodium storage performances. Abstract : Hierarchically nanostructured transition metal oxides are very attractive for electrochemical energy storage systems owing to the enhanced electrochemical performance induced by their unique microstructures. Herein, a hierarchical CoO microflower film is prepared by a low-temperature solvothermal method with subsequent annealing treatment. The CoO microflowers with an average size of about 6 μm consist of hexagonal nanosheets with a loose exterior layer, exhibiting a unique hierarchical micro–nanostructure. The hierarchical CoO microflower film electrode delivers a high capacity of 1297.9 mA h g −1 after 500 cycles at 454.5 mA g −1, manifesting superior lithium storage performance. The phenomenon of the lithium storage capacity increase during the initial 150 cycles is analyzed by comparing the galvanostatic discharge/charge voltage profiles at different cycles. For sodium storage, the CoO microflower film electrode shows a larger capacity of 277.8 mA h g −1 after 100 cycles at a current density of 90.9 mA g −1 . Based on the physical characterization results of the cycled film electrodes, the sodium storage mechanism of CoO is clarified.